Hábitos de estudio que utilizan los estudiantes de odontología y su relación con el rendimiento académico (2023)
Objective: To identify the study habits used by dental students and the relationship they have with academic performance. Description and methods: A descriptive, cross-sectional observational study was carried out, because this research was developed at a specific time, in which the relationship of the variables (academic habits and academic performance)